The Influence Of Islamic Brand Engagement As A Moderation Variable On Brand Loyalty In Bank Syariah Indonesia Customers - Chandra Warsito; Sofia Yustiani Suryandari; Pujiati; Nida Umi Farhah; Norailis Ab Wahab (Universitas Islam Negeri Profesor Kiai Haji Saifuddin Zuhri Purwokerto, 2026)
Non-Indexed Publication